New horizons in falls prevention and management for older adults: a global initiative - Montero-Odasso, Manuel; van der Velde, Nathalie; Alexander, Neil B; Becker, Clemens; Blain, Hubert; Camicioli, Richard; Close, Jacqueline; Duan, Leilei; Duque, Gustavo; Ganz, David A; Gómez, Fernando; Hausdorff, Jeffrey M; et al. (Age & ageing, 2021)
falls and fall-related injuries are common in older adults, have negative effects both on quality of life and functional independence and are associated with increased morbidity, mortality and health care costs. Current clinical approaches and advice from falls guidelines vary substantially between countries and settings, warranting a standardised approach. At the first World Congress on Falls and Postural Instability in Kuala Lumpur, Malaysia, in December 2019, a worldwide task force of experts in falls in older adults, committed to achieving a global consensus on updating clinical practice guidelines for falls prevention and management by incorporating current and emerging evidence in falls research. Moreover, the importance of taking a person-centred approach and including perspectives from patients, caregivers and other stakeholders was recognised as important components of this endeavour. Finally, the need to specifically include recent developments in e-health was acknowledged, as well as the importance of addressing differences between settings and including developing countries.a steering committee was assembled and 10 working Groups were created to provide preliminary evidence-based recommendations. A cross-cutting theme on patient’s perspective was also created. In addition, a worldwide multidisciplinary group of experts and stakeholders, to review the proposed recommendations and to participate in a Delphi process to achieve consensus for the final recommendations, was brought together.in this New Horizons article, the global challenges in falls prevention are depicted, the goals of the worldwide task force are summarised and the conceptual framework for development of a global falls prevention and management guideline is presented.
Gesehen am 06.10.2022